2005
DOI: 10.1021/jp052963w
|View full text |Cite
|
Sign up to set email alerts
|

How Active Is the Bend Excitation of Methane in the Reaction with O(3P)?

Abstract: The role of bending excitation of methane in the reaction with O(3P) is investigated in a crossed-beam experiment. Previous theories predicted that either stretch or bend excitation of the reactant promotes chemical reactivity and that initial bending excitation of CH4 preferentially yields umbrella-excited CH3 products. Experimentally, both predictions for bend-excited reagent were not borne out in this investigation. We found instead that compared to the ground-state reagent, bend-excited methane yields more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 44 publications
8
87
3
Order By: Relevance
“…[13][14][15]24,26 Only the relevant features are presented here. The O( 3 P)-atom beam was generated by photolyzing SO 2 (4−5% seeded in H 2 at total pressure of 12 atm) by an excimer laser at 193 nm near the throat of a PZT (piezoelectric translator) pulsed valve.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[13][14][15]24,26 Only the relevant features are presented here. The O( 3 P)-atom beam was generated by photolyzing SO 2 (4−5% seeded in H 2 at total pressure of 12 atm) by an excimer laser at 193 nm near the throat of a PZT (piezoelectric translator) pulsed valve.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[18][19][20][21][22][23] Zhang et al reported on the influences of the bending excitations of CD 4 and CHD 3 . 18 They found little rate-promotion and that when a bend-excited CD 4 /CHD 3 does react with O( 3 P), the initial bending energy, instead of flowing into the umbrella mode of methyl radical products as one might expect, is preferentially deposited into OD/OH vibrations. The former finding is now confirmed in a very recent theoretical study.…”
mentioning
confidence: 99%
“…We note in passing that the discharge-generated O less intense than the previous photolysis one. 17,18 A trade-off was made in this study for the convenience of changing E c . Figure 1 depicts the relevant energetics of this study.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17] There have also been studies on bend-excitation in the O + CH 4 reaction. [18][19][20] However, apart from very recent computational studies on the F + CH 4 ͑v 4 =1͒ and F + CH 2 D 2 ͑v 9 =1͒ reactions, 21,22 the previous work usually focused on the late-barrier polyatomic reactions ͑the transition state has a product-like structure͒ and there is almost no prior study on bending-excited early-barrier reactions, such as the F + methane reaction. Indeed the Polanyi rules 23 predict that the translational energy is more efficient to activate early-barrier reactions than vibrational excitation ͑and the reverse is true for the late-barrier reactions͒.…”
mentioning
confidence: 99%